The EFL Lecturers’ Feedback on Pre-Service Teachers’ Writing Performance In Online Instruction - Baiq Rabiatul Adawiyah; Baiq Sumarni (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2021)
Based on the facts about problems in teaching and learning of writing, it shows that the teaching learning of English in classrooms has not achieved the goals yet. Many students face many problems in writing. In addition, because of the situation happen in our world caused by Pandemic, it poses a special challenge for educators because in this situation learning takes place online. In this case, feedback is considered the most important factor in determining the success of the message to be conveyed to the recipient of the message. Concerning to the learning, Irons (2008) suggests that feedback is any information, process or activity carried out to accelerate student learning based on comments related to the results of assessing student development. In conducting a research entitled “The EFL Lecturers Feedback on Pre-Service Teacher Writing Performance in Online Instruction” in which this aims at identifying the types of feedback provided by lecturers on pre service teachers’ writing performance in online instruction and also to describe the implementation of the feedback provided by lecturers on pre-service teacher writing performance in online instruction. By means of applying interviews to 3 writing lecturers of faculty of culture, management, and business at UNDIKMA, the lecturer lecturers often used direct corrective feedback and electronic feedback in giving feedback on pre-service teacher writing performance in online instruction. The lecturers give some signs or clue to indicate the students writing mistakes, repeated explanations, add closeness to communication and give alternative answer for each students mistakes. It was also found that the feedback provide by the lecturers contain affective points. it also found that the implementation of lecturer feedback was more focused on general level feedback concerning the results of students' writing. the implementation of feedback emphasizes communication so that the feedback process can run smoothly, provides detailed explanations and gives students the opportunity to correct their mistakes in writing.